Genotypic Variation with Respect to Post-harvest Losses of Potato on Storage under Ambient Temperature - Mishra, Ashok; Kabi, Pragati; Ghosal, Debasish; Mohanty, A. K.; Mishra, Ananya; Das, Swarnalata; Sasmal, Arundhati (International Journal of Bio-resource and Stress Management, 2023)
The experiment was conducted at All India Coordinated Research Project on Potato, Odisha University of Agriculture and Technology, Bhubaneswar, Odisha, India during two different years (2016 and 2021) to study on the genotypic variation among 25 potato varieties with respect to post-harvest losses and storage. Approximately 5 kg potatoes of each genotype were kept inside perforated plastic containers under ambient temperature for this study. Rottage of tubers on number and weight basis were recorded at 30, 60, 75 and 90 days. Similarly sprouting of tubers in different genotypes was recorded at 75 and 90 days. It was observed that the percentage of tuber rottage on weight basis at the end of storage period (90 days) varied from 2.5% in Kufri Ashoka to 65.1% in Kufri Sinduri. There was also wide variation among different genotypes for sprouting at 75 and 90 days. Five genotypes did not sprout even at 90 days under storage at ambient temperature. Maximum storage loss of 86.9% was observed in Kufri Sinduri while minimum storage loss was recorded in Kufri Ashoka (8.5%). Highest direct effect on storage loss was exerted by percentage of rottage at 90 days. The direct effect of sprouting at 75 and 90 days on storage loss was very less clearly indicating its minor role. Weight loss of tubers of varying weights (20–40 g, 40–60 g and >60 g) in two varieties were also taken into consideration at 4, 7, 11, 18 and 26 days. The variety Kufri Pukhraj exhibited higher weight loss than Kufri Surya for all grades of tubers. The tubers weighing 20–40 g had the highest weight loss (1.22–2.81) among all the grades. However, the tubers of >60g showed the least weight loss in both the varieties.